Karakteristik Amilografi dan Sifat Pengembangan Tepung Singkong pada Optimasi Modifikasi Kombinasi Asam Laktat-Perlakuan Panas Lembap - Widanti, Yannie Asrie; Murdiati, Agnes; Pranoto, Yudi; Fibri, Dwi Larasatie Nur (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Although original properties of local flour have limited their uses in bread making, modification potentially enables them to become a viable option in the making of bakery products, aiming to substitute wheat flour. This study aimed to determine the optimum condition of lactic acid-HMT treatments for cassava flour. The amylographic characteristics of the flour and its effects on bread expansion were observed. A five-factor Box-Behnken design (lactic acid concentration, reaction time, HMT temperature, HMT time, and flour water content) was used, while the resulting data were analyzed using linear regression in Minitab software at a 5% significance level. The results showed that the treatment yielding modified cassava flour with high baking expansion was obtained at 0.5% lactic acid, 60 min reaction time, 30% flour water content, and temperature 140 °C for 1 h. Moreover, remarkable changes in pasting properties were observed after modification. The treatment increased peak, trough, and final viscosity but decreased breakdown viscosity. The morphology of modified flour differed from native one, with the former exhibiting more hollow granules and a flake-like structure.